A Review on Computational Fluid Dynamics Applications in the Design and Optimization of Crossflow Hydro Turbines - Mrope, Hamisi Ally; Chande Jande, Yusufu Abeid; Kivevele, Thomas T. (Journal of Renewable Energy, 2021)
In recent years, advances in using computational fluid dynamics (CFD) software have greatly increased due to its great potential to save time in the design process compared to experimental testing for data acquisition. Additionally, in real-life tests, a limited number of quantities are measured at a time, while in a CFD analysis all desired quantities can be measured at once, and with a high resolution in space and time. This article reviews the advances made regarding CFD modeling and simulation for the design and optimization of crossflow hydro turbines (CFTs). The performance of these turbines depends on various parameters like the number of blades, tip speed ratio, type of airfoil, blade pitch, chord length and twist, and its distribution along the blade span. Technical aspects of the model design, which include boundary conditions, solution of the governing equations of the water flow through CFTS, and the assumptions made during the simulations are thoroughly described. From the review, a clear idea on the suitability of the accuracy CFD applications in the design and optimization of crossflow hydro turbines has been provided. Therefore, this gives an insight that CFD is a useful and effective tool suitable for the design and optimization of CFTs.